PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOTOR HONDA BEAT - Thoriq Shofwan (2021)
The most popular motorbikes in Indonesia are still dominated by automatic motorbikes. The Honda All New Beat is one of the automatic motorbikes that is selling well in the market with the most competitive prices compared to other brands. Based on this background, this study aims to determine, prove and analyze the effect of price, product quality and brand image on purchasing decisions for Honda Beat motorbikes. This research is a quantitative study using the Multiple Regression Analysis method with the SmartPLS 3.0 analysis tool and a significance level of 5%. The data in this study were obtained from distributing questionnaires with a sample of 75 respondents using a Honda Beat motorbike in the Depok area and were selected randomly. The results of this study indicate an adjusted R square value of 0.745, and the conclusion of the hypothesis test is (1) there is a positive and insignificant effect between price on purchasing decisions with a magnitude of 0.147, (2) there is a positive and significant effect between product quality on purchasing decisions. with the magnitude of the influence of 0.325, and (3) there is a positive and significant influence between brand image on purchasing decisions with the magnitude of the influence of 0.454. Suggestions by researchers are for companies to analyze good strategies related to selling prices, product quality, and maintaining the image of the brand they have.